Preserving the Purpose of Procreation and Its Impact on the Decisions of International Fiqh Academy related to Medical Examination and Performing Operations - Maktoof, Rasul (PROSPECTIVE RESEARCHES, 2024)
Praise be to God, Lord of the Worlds, and the best blessings and peace be upon the chosen and trustworthy Prophet, our master Muhammad, and upon all his family and companions. After that, the study of the general objectives of Islamic law - preserving the religion, the soul, the mind, lineage, and wealth - is of great importance in the field of legal studies because of its impact in deducing legal rulings. This importance is confirmed and its impact is evident when studying contemporary emerging issues, such as medical, economic, political, etc., so this research was on the subject of (preserving the purpose of progeny and its impact on the decisions of the International Fiqh Academy related to medical examination and performing operations), so its study included an introduction, two sections, and a conclusion. In the introduction, the purpose of birth preservation and the International Jurisprudence Academy were defined. In the first requirement, the impact of the purpose of birth preservation on decisions related to premarital medical examination was addressed. In the second requirement, the impact of the purpose of birth preservation on decisions related to permission to perform operations was addressed, and finally, the most important results were reviewed recommendations in the conclusion